Exploring the mechanism of action of Jinqiancao granules against liver cirrhosis based on the liver-gut axis - Cheng, Fan-E.; Zhang, Yaxi; Zheng, Shihao; Qi, Wenying; Zhang, Xiaomei; Li, Size; Wang, Qiuyue; Zou, Xiangyun; Li, Xiaoke; Ye, Yongan; Zao, Xiaobin (Frontiers in Pharmacology, 2025)
BackgroundCurrent treatments for cirrhosis-a progressive disease marked by fibrosis and inflammation-are limited and non-specific. Jinqiancao granules (JQC), a traditional Chinese medicine used for hepatobiliary diseases, could provide a promising new therapeutic approach.PurposeThe objective of this study is to explore the therapeutic effects and potential molecular mechanisms of JQC on CCl4-induced liver cirrhosis in mice, and to analyze its effects on the liver-gut axis, including liver pathology, the intestinal barrier, and gut microbiota.MethodsTo investigate the therapeutic effects of JQC and its impact on the liver-gut axis, a mouse model of liver cirrhosis was established by intraperitoneal injection of carbon tetrachloride (CCl4). The mice were allocated into four groups: the control group (without CCl4 induction and receiving normal saline), the model group (CCl4-induced and receiving normal saline), and the two treatment groups which received JQC via gavage at either 500 mg/kg (JQC-H) or 250 mg/kg (JQC-L) after CCl4 induction. Upon completion of the treatment, all mice were euthanized to collect serum, fecal samples, liver, and intestinal tissues for subsequent analysis. The assessments encompassed histopathology (H&E, Masson, Picro Sirius Red), immunohistochemistry, immunofluorescence, molecular biology (ELISA, Western blot, qRT-PCR), transcriptomics, and 16S rRNA sequencing.ResultsJQC ameliorated CCl4-induced liver cirrhosis in mice by improving liver function and suppressing fibrosis, inflammation, and oxidative stress. Mechanistically, it modulated the PI3K-AKT pathway and restored gut-liver axis homeostasis. This was evidenced by intestinal barrier repair (including upregulation of ZO-1 and occludin, and reduction of LPS) and correction of microbial dysbiosis, specifically enriching beneficial bacteria, such as Bacteroidota and Akkermansia, that correlated negatively with liver injury.ConclusionThis study demonstrates that JQC mitigates liver cirrhosis in mice by modulating the gut-liver axis, enhancing the intestinal barrier, and inhibiting the PI3K-AKT signaling pathway. These results propose JQC as a promising therapeutic candidate, warranting further clinical translation.